Peripheral nervous system manifestations of Chediak‐Higashi disease. Issue 3 (16th December 2016) - Lehky, Tanya J.; Groden, Catherine; Lear, Barbara; Toro, Camilo; Introne, Wendy J.
ABSTRACT: Introduction: Chediak‐Higashi disease (CHD) is a rare autosomal recessive disorder with hematologic, infectious, pigmentary, and neurologic manifestations. Classic CHD (C‐CHD) presents in early childhood with severe infectious or hematologic complications unless treated with bone marrow transplantation. Atypical CHD (A‐CHD) has less severe hematologic and infectious manifestations. Both C‐CHD and A‐CHD develop neurological problems. Methods: Eighteen patients with CHD (9 A‐CHD and 9 C‐CHD) underwent electrodiagnostic studies as part of a natural history study (NCT 00005917). Longitudinal studies were available for 10 patients. Results: All A‐CHD patients had either sensory neuropathy, sensorimotor neuropathy, and/or diffuse neurogenic findings. In C‐CHD, 3 adults had sensorimotor neuropathies with diffuse neurogenic findings, and 1 adult had a sensory neuropathy. The 5 children with C‐CHD had normal electrodiagnostic findings. Conclusions: CHD can result in sensory or sensorimotor neuropathies and/or a diffuse motor neuronopathy. It may take 2–3 decades for the neuropathic findings to develop, because children appear to be spared. Muscle Nerve 55 : 359–365, 2017